Tingkat Kreativitas Guru Penjasorkes Dalam Memodifikasi Sarana dan Prasarana Penjas di Sekolah Dasar se-Kecamatan Bogor Utara (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the level of creativity of physical education teachers in modifying facilities and infrastructure in public elementary schools in north bogor district. The research method used is asurvey with a quantitative descriptive approach. Data collection techniques using a questionnaire and documentation. The research subjects in this study were physical education teachers at public elementary schools in north Bogor districts. The result of this study indicate that the creativity level of physical education teachers in modifying physical education facilities and infrastructure in public elementary schools the whole districts north bogor is in the very low category (8.33%), the lov category (8.33%), the medium category (58.33%), high category (25.00%), and very high category (0%). So the conclusion of the study is the level of creativity of physical education teachers in modifying physical educations facilites and infrastructure in north bogor districts is in the medium category. For suggestions, the physical education teacher should further improve and develop their creativity in the physical education learning process.